Characterization of excretory/secretory antigen from Toxocara vitulorum larvae - Starke-Buzetti, W. A.; Ferreira, F. P. (New York Acad Sciences, 2004)
Toxocara vitulorum is a nematode parasite of the small intestine of cattle and water buffalo, particularly buffalo calves between one and three months of age, causing high morbidity and mortality. The purpose of this research was to characterize the excretory/secretory (ES) antigens of T vitulorum larvae by SDS-polyacrylamide gel electrophoresis (PAGE) and Western blot (WB), using immune sera and colostrum of buffalo naturally infected by T vitulorum. The parasitological status of the buffalo calves was also evaluated using sequential fecal examinations. The results showed that the ES antigen revealed eight (190, 150, 110, 90, 64, 56, 48, and 19 kDa) protein bands by SDS-PAGE. The majority of these bands were recognized in the sera and colostrum of infected buffalo with T vitulorum when analyzed by WB. However, particularly fractions of high molecular weight (190, 150, 110, and 90 kDa) were represented in more prominent bands and persisted in the groups of buffalo calves at the peak of egg output, as well as during the period of rejection of T vitulorum by the feces of the calves. During the period of post-rejection of the worms (between the day 118 and 210 of age) the serum antibodies did not react with any protein bands. on the other hand, sera from buffalo calves at one day of age (after suckling the colostrum and at the beginning of infection) reacted with the same bands detected in the serum and colostrum of the buffalo cows.
Keywords: Toxocara vitulorum; water buffalo; ES antigen; immunity